Student startups and local economic development - Navid Bazzazian; Thomas Åstebro (European Regional Science Association (ERSA), 2010)
There has been an increased trend in the number of spin-offs generated by universities in the past thirty years. Past research reveals that the majority of these start-ups are located in the same region as the university from which they originated. In this paper, we investigate critically what universities do to encourage entrepreneurship to increase regional economic development. We will also discuss whether maximizing local entrepreneurship necessarily maximizes total welfare. Unfortunately, the scientific evidence reviewed in this paper indicates that policy changes at universities typically have very little impact on commercialization of research and the benefits to the universities are marginal. For example, current evidence indicates that creating incubators and science parks on university grounds have no discernable effects on local start-up rates. Further, from a theoretical perspective we have reviewed articles showing that introducing Technology Licensing Offices (TLOs), the most popular method to stimulate research commercialization, may likely introduce economic inefficiencies, hold-ups and decision biases that deviate from what is optimal. The median university among the top U.S. research-based institutions creates less than two academic spin-offs per year and so the relative effects on local economic conditions through TLO efforts and policies are bound to be marginal. Nevertheless the evidence also shows that the scientific stature of the faculty, the commercialization culture at the university, and the sheer number of science and engineering students graduated do have important positive effects on local start-up rates. Increasing expenditures on university staff and students causes increases in regional productivity growth and innovation and the marginal effects are much bigger in structurally weak regions. Evidence confirms that university spin-offs disproportionally favor local development. Maybe as much as 80 percent of all university spin-offs are and remain locally situated. However, universities that maximize local effects will not maximize their societal impact. Instead, it appears more efficient if universities simply try to maximize licensing revenues and not worry about the number of spin-offs and their locations.
Keywords: 330